Effects of combination therapy with Shenfu Injection in critically ill patients with septic shock receiving mechanical ventilation: A multicentric, real-world study - Li, Xiaoqian; Huang, Fan; Zhu, Lixia; Luo, Tianyi; Zhang, Yuzhuo; Gu, Huiwen; Guo, Liheng; Mao, Shuai (Frontiers in Pharmacology, 2022)
Background: Septic shock has increasingly become a cause of death threatening human survival. Shenfu Injection (SFI), a patented Chinese medicine, has been widely used in the treatment of patients with sepsis and cardiovascular diseases domestically. We sought to examine whether combination therapy with SFI can improve clinical outcomes in critically ill patients undergoing mechanical ventilation (MV). Methods: This real-world, multicenter retrospective trial enrolled consecutive adult patients with sepsis requiring MV from 4 medical/surgical intensive care units (ICUs) in China between August 2016 and September 2021. Patients were identified from the medical information department database of each center and assigned to either of 2 groups (SFI or control) on the basis of the initial treatment received. The primary outcome was 28-day all-cause mortality, and the durations of vasopressor therapy and MV, the ICU length of stay, and costs were assessed as secondary outcomes. Subsequently, we performed a meta-analysis of randomized controlled trials (RCTs) on SFI published before July 2021 to verify our conclusions. Results: 2311 mechanically ventilated patients with septic shock (1128 patients in the SFI group and 1183 in the control group) were analyzed. The survival probability during the first 28 days after admission in the SFI group was greater than that in the control group (P < 0.01 by log-rank test; hazard ratio [HR], 0.56; 95% confidence interval [CI], 0.39–0.72). Patients in the SFI group also experienced a significantly reduced duration of vasopressor therapy (7.28 [95% CI, 6.14–8.42] vs. 12.06 [95% CI, 10.71–13.41] days, P < 0.001), more ventilator-free days (6.49 [95% CI, 5.42–7.55] vs. 10.84 [95% CI, 9.59–12.09] days, P < 0.001), a shorter ICU length of stay (18.48 [95% CI, 17.59–19.38] vs. 23.77 [95% CI, 22.47–25.07] days, P < 0.001), and more time free from organ failure (14.23 [95% CI, 12.94–15.52] vs. 19.07 [95% CI, 16.09–22.05] days, P < 0.001). No major adverse effects were reported in either group. Conclusions: Among critically ill patients requiring MV, combination therapy with SFI can improve the survival probability without any obvious adverse reactions.